The effectiveness of non-exposure to incarceration in preventing COVID-19 and mitigating associated events: a systematic review and meta-analysis - Elida Lucia Carvalho Martins; Patrícia Constantino; Gustavo Laine Araújo de Oliveira (BMC Public Health)
Abstract Background For a long time, the penalty of imprisonment has been studied and criticized as ineffective in achieving the goals of resocialization and rehabilitation of offenders, and studies have associated incarceration with increased prevalence of disease. In response to the COVID-19 pandemic, the World Health Organization recommended decarceration as a prevention measure. The aim of this review was to analyze the effectiveness of non-exposure to incarceration in preventing COVID-19 and mitigating associated events. Methods We conducted a systematic review and meta-analysis of observational studies comparing the adult general population (GP) and incarcerated population (IP). Results We identified 1,334 publications without duplicates and extracted data from 22 studies. We found that COVID-19 incidence was 61% lower in the GP (RR = 0.39 [0.34, 0.45], p < 0.0001). Non-exposure to incarceration was associated with lower age- and sex-adjusted mortality (RR = 0.36, [0.27, 0.49], p < 0.0001). We did not find standardized data on age-adjusted case fatality. The hospitalized GP was older and showed a higher rate of obesity than the hospitalized IP; however, no statistically significant differences were found between the populations for admission to intensive care (RR = 0,91 [0.74, 1.13], p = 0.41) and hospital mortality (RR = 0.81 [0.54, 1.23], p = 0.32). Prevalence of the use of invasive mechanical ventilation was 23% lower in the GP (RR = 0.77 [0.70, 0.84, p < 0.0001). Conclusion Non-exposure to incarceration can be a strategy for preventing the spread of COVID-19 and reduces COVID-19 mortality in younger populations. Despite differences in age distribution and presence of comorbidities among the hospitalized GP and IP, we did not find any statistically significant differences between the two populations across most of the hospital-related outcomes. These findings should be interpreted with caution because it was not possible to determine a cause-and-effect relationship between the COVID-19 outcomes and exposure to incarceration. Registration PROSPERO CRD42023446610.